Normative Ambiguity of Cohabitation in Indonesia’s National Criminal Code - Shihaf Ismi Salman Najib; Sakti Boy Sihombing; Balqis Amalia; Fatikha Aisya Rahmi (Yayasan Sembilan Pemuda Indonesia, 2027)
This study examines the normative ambiguity of the cohabitation offense in Article 412 of Law Number 1 of 2023 concerning the Indonesian Criminal Code, particularly the absence of measurable temporal criteria and objective indicators for the phrase “living together as husband and wife outside marriage.” It employs legal research using statutory and conceptual approaches. Primary legal materials include the 1945 Constitution and the national Criminal Code, while secondary materials consist of criminal-law scholarship on legality, legal certainty, privacy, overcriminalization, and evidentiary standards. The materials were inventoried, classified, interpreted, and analyzed deductively. The study finds that Article 412 distinguishes cohabitation from adultery by focusing on an enduring domestic pattern rather than a single sexual act, yet it does not define the duration, frequency, continuity, or corroborating evidence required to establish that pattern. This omission grants broad interpretive discretion to investigators, prosecutors, and judges and may produce inconsistent, arbitrary, or discriminatory enforcement. The article proposes a cumulative operational framework based on sustained co-residence, repeated overnight presence, shared domestic routines, reciprocal representation as a household, and verifiable documentary or testimonial evidence. The framework offers a practical basis for implementing guidelines while preserving the complaint-based character of the offense, the principle of lex certa, due process, and constitutional privacy.